A qualitative analysis of Finnish RE students’ perceptions of their professional development during their initial teacher education - Viinikka, Kaisa (Journal of beliefs and values, 2021)
This article studies three RE (religious education) student teachers’ perceptions about their professional development from the beginning to the end of their initial teacher education. The focus of study was to investigate via an inductive content analysis if there are the same kind of phases in RE teacher education and how those phases are in relation to their training. Based on their characterisations of professional development, three phases were found: an explorative phase, a confirmatory phase and an induction phase. In the first phase, the typical things were uncertainty about the teaching profession and the importance of managing the content knowledge. In the second phase, it was observed by the interviewees that theory and practice could be combined and the development of different skills were seen as important. In the third phase, the interviewees perceived gaining experience from practice and combining their personal life and career as relevant. Finally, the interviewees believed that their professional development will continuously evolve. RE student teachers saw the various elements of their teacher education as important factors in all the phases.